Islamic Financial Literacy Islamic Financial Literacy: A Hybrid Systematic Literature Review and Bibliometric Analysis - Thoha, Muarif; Huda, Nurul (Journal of Economics and Business Aseanomics, 2025)
This study explores Islamic financial literacy through a hybrid approach that combines a Systematic Literature Review (SLR) and bibliometric analysis to provide a comprehensive and in-depth understanding of research developments in this field. Data were collected from the Scopus database for the study period up to May 8, 2025, using a structured keyword search strategy and strict selection criteria based on the PRISMA framework. The SLR method was employed to synthesize qualitative findings from relevant literature, while bibliometric analysis mapped research trends, author collaboration patterns, as well as keyword and citation distributions using VOSviewer and Bibliometrix software. The results indicate a significant increase in the number of publications and a diversification of research themes in Islamic financial literacy during the study period, with prominent research clusters focusing on financial education, financial behavior, and Islamic financial regulation. This hybrid approach not only strengthens the validity of the findings through the integration of qualitative and quantitative data but also offers a holistic view of the scientific dynamics and collaborative networks in the field of Islamic financial literacy. These findings are expected to serve as a strong foundation for the development of more effective and inclusive theories, policies, and practices in Islamic finance.